1986 International Electron Devices Meeting 1986
DOI: 10.1109/iedm.1986.191148
|View full text |Cite
|
Sign up to set email alerts
|

Sub-µm polysilicon super thin film transistor

Abstract: The application of poly Si super thin film transistors to VLSI technology, in which the active layer poly Si is 200-5OOA thick, has been investigated. The average grain size,of poly Si increased to more than lpm from 200-300A by solid phase recrystallization. Sub-um poly Si super thin film transistors and 19-stage CMOS ring oscillators were fabricated on 5inch insulator substrates. The mobility was about 100cm'/V.s for an N-channel and about 80cm2/V's for a P-channel transistor. The leakage current of transist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The available data on As distribution between the matte and the slag from several commercial bath smelting [38,41,42] and flash smelting [43] processes are presented in Figure 6 as a function of matte grade. The scatter in each set of plant data includes some variations in the process variables that affect As partitioning and possible errors or uncertainties in the determination of low levels of As in the matte or the slag.…”
Section: A Comparison Of Plant Datamentioning
confidence: 99%
See 4 more Smart Citations
“…The available data on As distribution between the matte and the slag from several commercial bath smelting [38,41,42] and flash smelting [43] processes are presented in Figure 6 as a function of matte grade. The scatter in each set of plant data includes some variations in the process variables that affect As partitioning and possible errors or uncertainties in the determination of low levels of As in the matte or the slag.…”
Section: A Comparison Of Plant Datamentioning
confidence: 99%
“…The calcium-ferrite-based slag has been used commercially in the Mitsubishi copperconverting process. [38] The distribution of As between the matte and the calcium ferrite slags at 1523 K (1250°C) under 0.1 atm SO 2 first was investigated by Acuna and Yazawa. [39] Roghani et al [40] also reported the distribution ratio of As between the calcium ferrite slag and the copper matte at 1523 K (1250°C) under varied SO 2 partial pressures.…”
Section: B Calcium Ferrite Slag and Matte Equilibriummentioning
confidence: 99%
See 3 more Smart Citations